Mengabadikan estetika; Fotografi dalam promosi pariwisata kolonial di Hindia-Belanda - Sunjayadi, Achmad (UI Scholars Hub, 2008)
When the first technology of photography came to the Netherlands-Indies in the nineteenth century, it was only used for government purposes and was not yet meant for public consumption. On the other hand, the rise of colonial tourism in the Netherlands-Indies in the early twentieth century required a medium for promotion. Photographs were the right choice because, as the saying goes, pictures could tell more than words. Photographs for colonial tourism promotions were produced in various forms such as postcards, illustrations in magazines and guide books, and were published by the colonial government as well as by private publishers. This article discusses the role of photography in colonial tourism in the Netherlands-Indies and its influence in the process to 'find Indonesia'. The sources used are taken from published postcard collections, magazines, guide books, and also published government archives.